Cardiac and Pulmonary Management Status of Duchenne Muscular Dystrophy in South Korea Based on Data From the National Health Insurance Database - Yoon, Jin A; Park, Ho Eun; Kim, Jinmi; Son, Jungmin; Shin, Yong Beom (Journal of clinical neurology (Seoul, Korea), 2022)
The purpose of this study was to determine the cardiac and pulmonary management status of patients with Duchenne muscular dystrophy (DMD) in South Korea based on the Korean National Health Insurance database.BACKGROUND AND PURPOSEThe purpose of this study was to determine the cardiac and pulmonary management status of patients with Duchenne muscular dystrophy (DMD) in South Korea based on the Korean National Health Insurance database.This study used data of patients with code G71.0 in the National Health Information database, and also those with the special case of code V012. Cardiac function was assessed based on whether echocardiography and 24-h electrocardiography were performed, as well as the frequency of these investigations. Furthermore, information on the use of angiotensin-converting enzyme inhibitors (ACEi), angiotensin II receptor blockers (ARB), and beta blockers (BB) in the drug benefit list was checked. Medical charge records were also checked regarding the prescription of respiratory functional assessments and treatments.METHODSThis study used data of patients with code G71.0 in the National Health Information database, and also those with the special case of code V012. Cardiac function was assessed based on whether echocardiography and 24-h electrocardiography were performed, as well as the frequency of these investigations. Furthermore, information on the use of angiotensin-converting enzyme inhibitors (ACEi), angiotensin II receptor blockers (ARB), and beta blockers (BB) in the drug benefit list was checked. Medical charge records were also checked regarding the prescription of respiratory functional assessments and treatments.The diagnostic criteria were met by 479 patients, with 41% of these patients receiving a cardiac evaluation, 29.8% being prescribed ACEi at 14.4±3.7 years of age, 59.5% undergoing pulmonary function tests, and 42.1% received pulmonary rehabilitation. The age at receiving ventilator support was 19.4±2.7 years. The frequency of cardiac and respiratory function tests increased with age, but the interval between tests was longer than the recent DMD care recommendations. The trend of taking ACEi, ARB, and BB for cardiac management in South Korea did not change during the study analysis period.RESULTSThe diagnostic criteria were met by 479 patients, with 41% of these patients receiving a cardiac evaluation, 29.8% being prescribed ACEi at 14.4±3.7 years of age, 59.5% undergoing pulmonary function tests, and 42.1% received pulmonary rehabilitation. The age at receiving ventilator support was 19.4±2.7 years. The frequency of cardiac and respiratory function tests increased with age, but the interval between tests was longer than the recent DMD care recommendations. The trend of taking ACEi, ARB, and BB for cardiac management in South Korea did not change during the study analysis period.The findings of this study will contribute to recognizing the current status and the importance of applying an anticipatory approach to cardiopulmonary function in DMD patients.CONCLUSIONSThe findings of this study will contribute to recognizing the current status and the importance of applying an anticipatory approach to cardiopulmonary function in DMD patients.